Navigating Shipbuilding Employee Performance through Work Motivation and Organizational Commitment in Surabaya - Putri Rahmatul Isti'anah; Fandi Fatoni; Anggra Olivia Anggela (Universitas Budi Luhur, 2026)
This study examines the effect of work motivation on employee performance with organizational commitment as a mediating variable in a shipbuilding company in Surabaya. The shipbuilding industry is a labor-intensive and skill-based sector that requires technical accuracy, interdepartmental coordination, discipline, and employee reliability. This research used a quantitative explanatory design involving 58 employees selected through saturated sampling because the entire population was included as respondents. Data were collected using a Likert-scale questionnaire and analyzed through Partial Least Squares Structural Equation Modeling. The findings show that work motivation significantly affects employee performance and organizational commitment, while organizational commitment significantly affects employee performance and mediates the relationship between work motivation and employee performance. Although the structural relationships are statistically supported, the relatively low explanatory power of the model indicates that employee performance is also influenced by other managerial and organizational factors. The study concludes that performance improvement in the shipbuilding industry should not rely solely on motivational practices, but also on strengthening employees' organizational commitment through fair rewards, appropriate work placement, clear job descriptions, supportive leadership, and welfare-oriented human resource policies. The findings offer practical implications for human resource management in maritime-related industries.